2002
DOI: 10.1046/j.1440-1827.2002.01358.x
|View full text |Cite
|
Sign up to set email alerts
|

Bcl‐2, iNOS, p53 and PCNA expression in normal, disordered proliferative, hyperplastic and malignant endometrium

Abstract: We attempted to determine Bcl-2, inducible nitric oxide synthase (iNOS), p53 and proliferating cell nuclear antigen (PCNA) expression, and the relationships between them, in endometrioid adenocarcinomas and precursor lesions. Expression of Bcl-2, iNOS, p53 and PCNA were investigated immunohistochemically in 91 samples from benign (proliferative (pEM), secretory (sEM), disordered proliferative (dEM), inactive/atrophic (aEM), hyperplastic endometrium) and malignant endometrial tissue. Staining scores for Bcl-2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…35 Cinel et al reported that p53 positivity was not determined in normal endometria outside a few tubal metaplasia areas. 36 Our results were also similar. The metaplastic cells of anovulatory DUB causes may simulate endometrial hyperplasia and endometrial adenocarcinoma, leading to difficulty in cytologic interpretation.…”
Section: Endometrial Immunocytochemistrysupporting
confidence: 80%
“…35 Cinel et al reported that p53 positivity was not determined in normal endometria outside a few tubal metaplasia areas. 36 Our results were also similar. The metaplastic cells of anovulatory DUB causes may simulate endometrial hyperplasia and endometrial adenocarcinoma, leading to difficulty in cytologic interpretation.…”
Section: Endometrial Immunocytochemistrysupporting
confidence: 80%
“…Altogether 20 observational studies with a total of 1,278 specimens (137 proliferative endometrium, 676 endometrial hyperplasia, and 465 endometrial cancer), were included in the systematic review. The flow diagram reporting the process of study selection is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…In head and neck cancer, excessive NO correlates with cancer risk and metastatic potential (52, 108,109), and in colorectal cancer increased NO leads to enhanced angiogenesis and invasiveness (110,111). Elevated NO concentrations have also been correlated with endometrial, cervical and gastric cancers, and tumors of the central nervous system (112)(113)(114)(115)(116)(117)(118). For these conditions, however, there is currently no targeted approach for intervention of NO production available for clinical use.…”
Section: The Dual Role Of Nitric Oxide In Cancermentioning
confidence: 99%